2016
DOI: 10.1108/wjemsd-08-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marketing culture and organizational commitment

Abstract: Purpose – The purpose of this paper is to find out whether there was a significant relationship between marketing culture and organizational commitment. In addition, relations between dimensions or marketing culture and dimensions of organizational commitment were investigated. Prior studies have shown that there were significant relationships between organizational culture and organizational commitment. Accordingly it is that there is a significant relationship between marketing culture and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(34 reference statements)
4
14
0
1
Order By: Relevance
“…They are proud to be part of the organization and choose not to leave the organization thereby creating employee commitment to the organization. The results of this study are in line with the results of Yildirim et al (2016); Islam et al (2013); Acar (2012); Gokce et al (2014); Sikorska-Simmons (2006), which concluded that organizational culture influences organizational commitment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…They are proud to be part of the organization and choose not to leave the organization thereby creating employee commitment to the organization. The results of this study are in line with the results of Yildirim et al (2016); Islam et al (2013); Acar (2012); Gokce et al (2014); Sikorska-Simmons (2006), which concluded that organizational culture influences organizational commitment.…”
Section: Discussionsupporting
confidence: 90%
“…Employees who view culture in their organization as fair and respectful of their employees will have a higher level of organizational commitment. Yildirim et al (2016), found that marketing organizational culture greatly affects affective commitment. Marketing culture creates more participatory management in organizations and provides strong coordination between organizational and employee goals.…”
Section: Relationship Of Organizational Culture and Organizational Comentioning
confidence: 99%
See 2 more Smart Citations
“…Market culture emphasizes rationalized actions culminating into efficient and productive planning of achieving organizational goal settings. Market culture orientation was found to have influenced organizational commitment through its impact on behaviour pattern of employees in diverse organizations (Yildirim, Acaray and Candan, 2016).Individuals are expected to understand the corporate values and expectations of the organization and the relevance of each and every role, thereby inspiring and motivating employees' commitment in achieving organizational goals (Cameron et al, 2011) …”
Section: The Market Culturementioning
confidence: 99%